2022
DOI: 10.1002/ca.23885
|View full text |Cite
|
Sign up to set email alerts
|

Movement of the superior mesenteric artery in patients with superior mesenteric artery syndrome: A case‐reference study

Abstract: Superior mesenteric artery (SMA) syndrome is related to the reduction of the aortomesenteric angle on detailed imaging studies; i.e., an expert's ultrasonography or angiography. We aimed to test a simpler imaging finding of SMA syndrome. This cross-sectional case-reference study examined whether right movement of the SMA on unenhanced computed tomography (CT) is useful for the diagnosis of SMA syndrome. We reviewed hospital records of patients admitted in 2008-2018. Each case was matched to one non-case patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Although it is believed that positioning the patient in the left lateral position is effective in the treatment of SMA syndrome, there is little evidence[ 13 , 16 ]. The optimal body position for each patient may vary because recent studies found a variation in the SMA position and movement[ 14 , 15 , 17 ]. Case 1 in our report demonstrated better content passage in the right lateral position than the left, corroborating the findings of Khan et al [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is believed that positioning the patient in the left lateral position is effective in the treatment of SMA syndrome, there is little evidence[ 13 , 16 ]. The optimal body position for each patient may vary because recent studies found a variation in the SMA position and movement[ 14 , 15 , 17 ]. Case 1 in our report demonstrated better content passage in the right lateral position than the left, corroborating the findings of Khan et al [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Case 1 in our report demonstrated better content passage in the right lateral position than the left, corroborating the findings of Khan et al [ 15 ]. Miyata et al [ 17 ] reported a variation in position of SMA demonstrating that major position was the right side along with the aorta[ 17 ]. No study has reported the optimal position in SMA syndrome[ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positioning the patient in the left lateral or sitting position should be helpful[ 95 , 130 ]. However, the best position for each patient may vary because recent studies revealed there is a variation of the SMA position and movement[ 131 - 133 ]. In addition to gastric tube suction, intravenous metoclopramide can enhance gastrointestinal motility and help decompression[ 134 , 135 ].…”
Section: Treatmentsmentioning
confidence: 99%
“…The absence of visceral and retroperitoneal fat results in an angle between the AA and the SMA that is usually 6-25°, as opposed to the normal range of 38-56°, which can induce this uncommon and potentially fatal illness [ 3 ]. The aortomesenteric distance is also 2-8 millimeters instead of 10-20 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%